Implementing Religious Moderation and Tolerance Attitude in Akidah Akhlak Learning - Ali Sabri; Wahyuddin Nur Nst; Siti Halimah (Nazhruna: Jurnal Pendidikan Islam, 2022)
This article aims to find the implementation of religious moderation and the formation of student tasamuh attitudes at MAS Al Huda, Pangkalan Susu district. This research is qualitative, collecting data through observation, interviews, and documentation studies. Primary data sources in this study include; principals, teachers of Akidah Akhlak, School Public Relations, and PKS 3 for Student Affairs and Students. The next step of data analysis is collecting data, reducing data, presenting data, and concluding data. The results of the study revealed that planning was carried out during the preparation of the syllabus and included matters relating to religious moderation in the material of Akidah akhlak. While implementing learning, the teacher uses learning methods that follow the material, such as the lecture method, and even prioritizes group discussions to instill a moderate attitude in students, namely mutual respect, respect, being fair to group friends, and being sporty during the learning process. The implication is that it has an impact on the attitudes that are built in students, such as students having better religious attitudes and social attitudes, such as being obedient to worship, respecting others, establishing intimacy, having social care, having a nationalist spirit, being tolerant, and obeying the rules.